Earth kulintang [soundrecording] - Aves, Bob; Balce, Baba; Butocan, Aga Mayo; Nono, Grace (Tao Music, 1995)
A collection of traditional Maguindanaoan kulintang solos performed by Aga Mayo Butocan. Jux taposed with a tapestry of sounds from the lake, the sea, and the rainforest, it is a re-creation of wild mother earth, supreme nurtures of our creative identities.